Implementasi Kebijakan Pelayanan 24/7 dalam Meningkatkan Pelayanan Pengguna Jasa pada Kantor Pengawasan dan Pelayanan Bea dan Cukai Tipe Madya Pabean Belawan - Darwin Martua Sinaga; Budi Hartono; Ina Triesna Budiani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The issuance of Minister of Finance Decree Number 504/PMK.04/2009 on 24-Hour Customs Service and 7-Day Customs Office at Certain Ports accommodates customs services to facilitate importers or exporters in submitting customs documents in order to obtain service certainty so that imported or exported goods can be served. However, some obstacles related to 24/7 services were found which may cause user satisfaction to be less than optimal. This study aims to determine the implementation of the 24/7 Service Policy and the factors affecting its implementation at the Belawan Customs and Excise Supervision and Service Office in North Sumatra. The method used is descriptive qualitative with data collection conducted through observation, interviews, and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawing. Based on the results of the study, it is known that the implementation of the 24/7 Service Policy in improving user services at the Belawan Customs and Excise Supervision and Service Office, North Sumatra, still needs improvement due to communication, resources, and bureaucratic structure that have not been running well, influenced by factors such as Standard Operating Procedures (SOP), widespread fragmentation, limited socialization, and officer competence. Meanwhile, the implementation is supported by disposition influenced by factors such as facilities, authority, and performance contracts.